2021
DOI: 10.3390/pharmaceutics13040571
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Alcohol-Based Hand Sanitizers for Long-Term Use, Formulated with Addition of Natural Ingredients in Comparison to WHO Formulation 1

Abstract: During the spread of COVID-19, many laboratories used the “Formulation 1” proposed by the World Health Organization to prepare hand sanitizers. Taking into consideration its ingredients and the prolonged use of hand sanitizers, “Formulation 1” (P1) was compared with two gel formulations (P2 and P3) prepared with the addition of natural emollients and two different viscosity enhancers to define their chemical–physical stability, biocidal efficacy, and in vivo acceptability and tolerability. P1 resulted in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…For the in-vitro biocide efficiency using the time kill assay procedure to check for the reduction of viable cells of the bacterial strains and fungi strains. Previous studies [29] have reported that a substance is considered biocide when there is a reduction in the viable cells of at least 10 5 after a maximum of 5 min for a bacterial strain and 15 min for a fungi strain. However, in this study, it was observed that the highest microbial death for Salmonella typhi, was 88% using F2, which occurred at 75secs, and 70.3% at time 75secs.…”
Section: Resultsmentioning
confidence: 99%
“…For the in-vitro biocide efficiency using the time kill assay procedure to check for the reduction of viable cells of the bacterial strains and fungi strains. Previous studies [29] have reported that a substance is considered biocide when there is a reduction in the viable cells of at least 10 5 after a maximum of 5 min for a bacterial strain and 15 min for a fungi strain. However, in this study, it was observed that the highest microbial death for Salmonella typhi, was 88% using F2, which occurred at 75secs, and 70.3% at time 75secs.…”
Section: Resultsmentioning
confidence: 99%
“…MimicLipid MSM-1000 is botanical surfactant that forms hydrogen bonding with the chlorine dioxide to make the stable multi-lamellar and micelles [12]. Solubil EWG-1100 (2) Bio-PhyroPGI-250 (3) Dipropylene Glycol Water Chlorine dioxide 100ppm solution Chlorhexidine digluconate 20% soln. - (3) Bio-PhyroPGI-250: Glycereth-25 PCA Isostearate.…”
Section: Manufacturing Of Hydrophilic O/w Emulsionmentioning
confidence: 99%
“…Solubil EWG-1100 (2) Bio-PhyroPGI-250 (3) Dipropylene Glycol Water Chlorine dioxide 100ppm solution Chlorhexidine digluconate 20% soln. - (3) Bio-PhyroPGI-250: Glycereth-25 PCA Isostearate.…”
Section: Manufacturing Of Hydrophilic O/w Emulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gels are obtained by incorporating a viscosity enhancer into the diluted alcohol. A wide variety of gelling agents approved for pharmaceutical and cosmetic products can be used for that purpose, but the most employed in ABHS formulations are cellulose derivates, such as Hydroxypropylmethylcellulose (HPMC) (e.g., Nutragel, NutraBe) and Hydroxyethylcellulose (HEC) (e.g., Hygienizing gel, Kaleido Studio), and carbopol (e.g., DermoGel, Glenova cosmetics) [ 16 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%